1987
DOI: 10.1136/jnnp.50.11.1442
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological studies in acute organophosphate poisoning.

Abstract: SUMMARY Electrophysiological studies in suicidal patients with organophosphate poisoning are reported. Patients often developed muscular weakness of variable severity owing to diplorisation block at nicotinic receptors. During such paralysis nerve conduction velocity and distal latencies were normal even in severely paralysed patients. The amplitude of the compound action potential was smaller than in controls and often showed a repetitive response. The amplitude tended to be lower in those more severely affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
49
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 9 publications
2
49
0
Order By: Relevance
“…3,17 Our data suggest that respiratory muscle (diaphragmatic) weakness is a major contributing factor in the development of respiratory failure in acute OP poisoning. Reduced amplitudes of the diaphragmatic CMAPs were noted in 60% of initial neurophysiological studies.…”
Section: Discussionmentioning
confidence: 97%
“…3,17 Our data suggest that respiratory muscle (diaphragmatic) weakness is a major contributing factor in the development of respiratory failure in acute OP poisoning. Reduced amplitudes of the diaphragmatic CMAPs were noted in 60% of initial neurophysiological studies.…”
Section: Discussionmentioning
confidence: 97%
“…In severe poisoning, patients may have convulsive seizures. 8 Muscarinic, Nicotinic, and CNS symptoms according to amount of poisoning are observed in observation. We found that 41.5% patients were unable to tell the amount of poisoning, 24.4% patients had taken less than 5 grams, and 34.1% patients had taken more than 5 grams of poison.…”
Section: Discussionmentioning
confidence: 97%
“…In patients with severe OP intoxication, abnormalities suggestive of membrane instability (positive sharp and fibrillation potentials) can occur. 4,6 In conclusion, patients with IMS can be monitored with electrophysiological studies, and the results correlate well with clinical findings in acute OP poisoning. 1,7-9…”
mentioning
confidence: 81%